Valorization of residues from refining of used vegetable oils (2014)
This study investigates the advantages of two-phase anaerobic digestion for treating a mixture (1/5 v/v) of used vegetable oils processing wastes and pig manure using two semi-continuous digesters operated at mesophilic temperature (37±1 ºC). The experiments were conducted at hydraulic retention times (HRT) of 0.5, 1, 2 and 4 days in the first stage (acidifier) and at HRT of 11.5, 15, 18 and 20 days in the second stage (methanizer). The results revealed that the HRT had a high influence on the soluble chemical oxygen demand (CODs) and total dissolved solids (TDS) removal. The maximum total CODs removal efficiency of 86.4% and TDS removal efficiency of 81.9% was achieved at 20 days of global HRT. The maximum biogas production of 0.65 m3 per kilogramme of volatile dissolved solids (VDS) removed (65% CH4) was also achieved at 20 days of HRT.